Control of fibrosis with enhanced safety via asymmetric inhibition of prolyl‐tRNA synthetase 1 - Ina Yoon; Sulhee Kim; Minjae Cho; Kyung Ah You; Jonghyeon Son; Caroline Lee; Ji Hun Suh; Da‐Jeong Bae; Jong Min Kim; Sinae Oh; Songhwa Park; Sanga Kim; et al. (EMBO Molecular Medicine)
Abstract Prolyl‐tRNA synthetase 1 (PARS1) has attracted much interest in controlling pathologic accumulation of collagen containing high amounts of proline in fibrotic diseases. However, there are concerns about its catalytic inhibition for potential adverse effects on global protein synthesis. We developed a novel compound, DWN12088, whose safety was validated by clinical phase 1 studies, and therapeutic efficacy was shown in idiopathic pulmonary fibrosis model. Structural and kinetic analyses revealed that DWN12088 binds to catalytic site of each protomer of PARS1 dimer in an asymmetric mode with different affinity, resulting in decreased responsiveness at higher doses, thereby expanding safety window. The mutations disrupting PARS1 homodimerization restored the sensitivity to DWN12088, validating negative communication between PARS1 promoters for the DWN12088 binding. Thus, this work suggests that DWN12088, an asymmetric catalytic inhibitor of PARS1 as a novel therapeutic agent against fibrosis with enhanced safety.